أوجه الشبه والاختلاف بين قصتي يوسف وموسى من خلال سورتي يوسف والقصص: دراسة موضوعية - حسين، أسامة عبدالرحيم محمد (جامعة الأزهر - كلية أصول الدين والدعوة بالمنوفية, 2019)
يدور هذا البحث حول دراسة قصتي نبيي الله يوسف وموسى ( )، كما وردتا في سورة (يوسف والقصص) في محاولة للوقوف - موضوعيا - على أوجه التشابه والاختلاف بينهما من حيث إن السورتين الكريمتين فد استفاضتا في سرد قصة الرسولين العظيمين منذ المولد إلى النهاية؛ فبينهما وجوه متقاربة، وأحوال متشابهة ويعض الفروق الملحوظة؛ ولعل هذا مرتبط بشكل كبير بالأحداث المثيرة التي شهدتها كل قصة، وارتباطهما بتطورات تاريخية ونوع من الصراع بين الحق والباطل، والتشابه في المخاطر التي تعرض لها كل نبي. عن طريق استقراء التفسير الموضوعي للآيات الكريمة محل البحث دون استطراد لتفسير السورتين تفسيرا تحليليا -قدر المستطاع - وصولا إلى مجموعة من وجوه التشابه ونقاط الخلاف التي حظيت بها كل قصة في السورتين، للوقوف على العبر المستفادة من كل قصة، وغير ذلك من النتائج المهمة في هذا السياق. ويضم البحث في طياته تمهيدا وثلاثة مباحث: • أما التمهيد: وتناول فيه الحديث عن مفهوم القصة في اللغة والاصطلاح، كما عرضت لأنواع القصص كما وردت في القران الكريم، ثم التعريف بالنبيين الكريمين، كذلك ألقيت ضوءا كاشفا على سورتي (يوسف، القصص). المبحث الأول: وتناول جانبا من حياة يوسف وموسي ( ) من حيث النشأة والطفولة وحياة القصور. • المبحث الثاني: وجاء الحديث فيه عن رحلة الابتلاء والاختبار التي شهدها كل منهما. • المبحث الثالث: وقد تناول ما آلت إليه أحداث قصتيهما، والنهاية السعيدة التي جمعت بينهما.
This research revolves around the study of the stories of the prophets of Joseph and Moses, peace be upon them, as mentioned in Surat (Joseph and stories) in an attempt to objectively - to look at the similarities and differences between them, in that the two suras have elaborated on the story of the two great apostles, from birth to the end These are closely related to the dramatic events of each story, their association with historical developments and a kind of conflict between truth and falsehood, and the similarity in the dangers to which each prophet was exposed. By extrapolating the objective interpretation of the verses in question, without further digressing the interpretation of the two Surat analytical interpretation - as much as possible - to reach a set of similarities and points of disagreement enjoyed by each story in the two Surat, to find out the lessons learned from each story, and other important results in This context. The research includes a prelude and three topics: The preamble: dealt with talk about the concept of the story in the language and terminology, as presented to the types of stories as contained in the Koran, and then the definition of the prophets, as well as a spotlight on my wall (Joseph, stories) The first topic: and dealt with part of the life of Joseph and Moses - peace be upon them - in terms of development and childhood and life of palaces. The second topic: The talk about the journey of affliction and testing witnessed by each. The third topic: has dealt with the events of their stories, and the happy ending that brought them together.
Keywords: علوم القرآن -- علم التفسير -- القصة القرآنية -- يوسف، عليه السلام -- موسى، عليه السلام -- سورة يوسف -- سورة القصص